What is Halal Gastronomy? - Rahayu, Solihah Sari; Rusydiana, Aam Slamet (Journal of Islamic Economics Literatures, 2024)
This study aims to see the development of research on the topic of "Halal Gastronomy" and research plans that can be carried out based on journals published on the theme. This research uses qualitative method with bibliometric analysis approach. The data used is secondary data with the theme "Halal Gastronomy" which comes from the Dimension database with a total of 16 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Halal Gastronomy" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research with the theme "Halal Gastronomy" were Ningsih, Caria; and Hatta, Farah Ayuni Mohd. Furthermore, based on bibliometric keyword mapping, there are 4 clusters with the most used words including tourism, gastronomy, halal food, culture, and destination. Then, the topics of research paths related to Halal Gastronomy are Halal Gastronomic Tourism in Indonesia, Celebrity Chefs and Halal Gastronomy, Opportunities in Halal Gastronomy Tourism, and Gastronomy Elements in Halal Context.